Water Saving for Paddy Cultivation Under the System of Rice Intensification (SRI) in Eastern Indonesia - Mohammad Hasan; Shuichi Sato (Jurnal Ilmu Tanah dan Lingkungan, 2007)
The System of Rice Intensification (SRI) developed in Madagascar in 1980s is a revolutionary new idea for paddycultivation to increase yields with reduced external resources. Basic idea of SRI originally proposed (Basic SRI) is to applycombination of (a) transplanting of young seedlings with wider spacing and (b) intermittent irrigation during vegetativegrowth period Further, application of organic fertilizers without use chemicals has practiced as "Organic SRI" as an idealapproach to improve soil and to produce high quality rice. Over the past fIVe years, a Japan-funded irrigation project inEastern Indonesia executing by the Directorate General of Water Resources, the Ministry of Public Works has introduced SRIand assessed it's potential to reduce demandfor irrigation water while rewardingfarmers with higher production and incomes.This paper reports on on-farm comparative evaluations conducted over 9 seasons between 2002 and 2006 across 8 provincesunder DISIMP. It summarizes the results of 12,133 comparison trials that covered a total area of 9,429 hectares. Averageyield increase was 78% (3.3 tlha) with reductions of 40% in water use, 50% in fertilizer applications, and 20% in the costs ofproduction. As a conclusion, SRI practices can achieve significantly higher output of rice with a reduction in inputs, enhancingsimultaneously the productivity of the resources (land, labor, water and capital) used in irrigated rice production. Theeconomic attractiveness of SRI methods is very great, giving farmers strong incentive to accept water-saving as new norm forirrigated rice production.